2002
DOI: 10.1017/s101423390000153x
|View full text |Cite
|
Sign up to set email alerts
|

Deoni cattle breed of India. A study on population dynamics and morphometric characteristics

Abstract: cuanto a la conservación y la mejora ambos modelos necesitán ser mejorados para conseguir un programa de éxito.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
14
3
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 0 publications
7
14
3
2
Order By: Relevance
“…As there was no report on FSP in Deoni cattle, comparison was made with pooled service period. The FSP estimated was similar to the pooled service period of previous studies as 184.2 ± 4.6 (Deshpande et al, 1977d) and 170.0± 7.0 days (Singh et al, 2002). Higher CV value for FSP in the present study revealed large scale of variation in the FSP of Deoni cattle.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…As there was no report on FSP in Deoni cattle, comparison was made with pooled service period. The FSP estimated was similar to the pooled service period of previous studies as 184.2 ± 4.6 (Deshpande et al, 1977d) and 170.0± 7.0 days (Singh et al, 2002). Higher CV value for FSP in the present study revealed large scale of variation in the FSP of Deoni cattle.…”
Section: Resultssupporting
confidence: 89%
“…The mean age at first calving is higher than the previous report in this breed (38.73 ± 0.73 months) by Das et al, (2011). However, the estimated mean AFC in the present study was lower than the previous reports on Deoni cattle reported by Deshpande et al, (1977a) and Singh et al (2002). Estimated CV value of the studied population indicated higher variation of AFC than the value (11.2 per cent) reported by Deshpande et al, (1977a) in the same breed.…”
Section: Resultscontrasting
confidence: 80%
See 1 more Smart Citation
“…In earlier studies of Indian native cattle, the major focus was on assessment of morphological parameters and information gained from local sources (Nivsarkar et al 2000;Joshi et al 2001;Singh et al 2002;Gaur et al 2003;Karthickeyan et al 2006). Recently, assessment of genetic diversity and delineation of the genetic structure of cattle breeds have become a major concern, as some of the important populations and breeds are either declining or breed characters are being diluted under the present production system.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, categorization of these cattle breeds has often been based on morphological data and information gained from the local breed keepers. 1,[4][5][6][7] Hence, an effort to deduce the genetic structure among the Indian native cattle breeds becomes pertinent for the development of future management strategies. For this purpose, microsatellites markers previously exploited for diversity studies in cattle populations from Africa, Europe, and Asia [8][9][10][11][12][13][14] are utilized herein to characterize Indian native cattle breeds.…”
mentioning
confidence: 99%